О сверхнизком пороге генерации полупроводникового КРС лазера - Алексанян, Ал. Г.
A model calculation of the threshold current of a laser in quantum well structure is presented. This cumulation shows that factor at the lasing wave length is lager than the value estimated at energy gap of bulk semiconductors.
Keywords: Электротехника